Products & Technology: 3.5 billion hours of nurse time released by 2030: Potential efficiency gains from shared care and longwear advanced foam dressings. Issue 2 (2022) - Moore, Zena; Loney, Amanda; Probst, Sebastian; Ryan, Hayley; Milne, Catherine; Meaume, Sylvie
No abstract available